Building Sustainability according to Integral Theory and the Quadrant Analysis-Case study: Baghdad Municipality Building as an example (Journal of Architectural Design, 2025)
The research examines the extent to which a building incorporates sustainability principles, by applying an integral theory. The research problem lies in the lack of clarity regarding the application of sustainability concepts in building design, within the framework of the proportional relationship between the building and nature. This resulted in buildings that are not compatible with nature and negatively impact the environment and climate. The research aims to study and analyze the building according to the integral theory and apply its four quadrants to the building, and to come up with indicators that determine the building's adoption of the sustainability initiative. The research process begins by examining the global trend towards sustainability, focusing on the impact of architecture on the environmental balance, and the resulting climate change, global warming, and negative effects on the environment. Then, the discussion moves on to the concept of unsustainable architecture, its depletion of resources and energy, and its negative impact on human health and well-being. Subsequently, the integral theory was applied on an administrative building in the capital city of Baghdad as an example, to determine how well the building actually implements the four quadrants of the theory in practice, and to come up with a final indicator of the building's level of sustainability